ESTUDO FITOSSOCIOLÓGICO EM CANTEIROS DE FORRAGEIRAS SUBMETIDAS OU NÃO A SOMBREAMENTO - Acunha, Rubia Mara; Melville, Luisa; Gomes, Redney; Balbuena, Robson; Dos Santos, Patricia; Copeti, Daniela (ANAIS DO ENIC, 2018)
-